Development and Validation of a High-Performance Liquid Chromatography Method to Quantify Marker Compounds in Lysimachia vulgaris var. davurica and Its Effects in Diarrhea-Predominant Irritable Bowel Syndrome - Hye-Youn Kim; Cho-Een Kim; Dool-Ri Oh; Yonguk Kim; Chul-Yung Choi; Jaeyong Kim (Molecules, 2024)
Irritable bowel syndrome (IBS), a common gastrointestinal disorder worldwide, is characterized by chronic abdominal pain, bloating, and disordered defecation. IBS is associated with several factors, including visceral hypersensitivity, gut motility, and gut–brain interaction disorders. Because currently available pharmacological treatments cannot adequately improve symptoms and may cause adverse effects, the use of herbal therapies for managing IBS is increasing. Lysimachia vulgaris var. davurica (LV) is a medicinal plant used in traditional medicine to treat diarrhea. However, information on whether LV can effectively improve diarrhea-predominant IBS (IBS-D) remains limited. In this study, using an experimental mouse model of IBS-D, we elucidated the effects of the LV extract. The methanol extract of LV decreased fecal pellet output in the restraint stress- or 5-hydroxytryptamine (5-HT)-induced IBS mouse model and inhibited 5-HT-mediated [Ca2+]i increase in a dose-dependent manner. Furthermore, we developed and validated a high-performance liquid chromatography method using two marker compounds, namely, chlorogenic acid and rutin, for quality control analysis. Our study results suggest the feasibility of the methanol extract of LV for developing therapeutic agents to treat IBS-D by acting as a 5-HT3 receptor antagonist.